Wireless Sensor Networks: VAN-Project Perspectives - Lakkundi, Vishwas; Kraetzig, Marko (Společnost pro radioelektronické inženýrství, 2009)
The emergence of wireless sensor networks and their potential for a multitude of novel applications, especially in the industrial automation domain, are noteworthy. This paper presents research and development perspectives on wireless sensor networks from the Virtual Automation Networks project in terms of prototype development and coexistence with other chosen wireless technologies. The project-specific design and specification aspects, implementation and integration issues, and coexistence tests, measurements and results are covered in detail. The paper illustrates the successful integration of wireless sensor networks into the overall prototype and shows that they can coexist with other wireless technologies.
Keywords: Wireless sensor networks; industrial automation; ZigBee; wireless prototypes; coexistence of wireless technologies